2018
DOI: 10.1080/15563650.2018.1487563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional status on acetaminophen measurement and exposure

Abstract: Short-term fasting increases acetaminophen exposure in healthy subjects, whereas no effect is observed after a high-fat diet. Furthermore, short-term fasting decreases the accuracy of the enzymatic colorimetric method when measuring relatively low acetaminophen concentrations. This suggests considering nutritional status when assessing the risk of acetaminophen-induced toxicity, although further research at toxic doses is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…A recent study showed a ~10% decrease in therapeutically dosed acetaminophen clearance in healthy men who had fasted for 36 h 13 . Similarly, a reduction in clearance of roughly 15% was found in men who had fasted for 36 h 14 . Overall, both in animals and humans an apparent effect of malnutrition is increased exposure to total acetaminophen due to a decreased clearance, clinically presented as an increased t½.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A recent study showed a ~10% decrease in therapeutically dosed acetaminophen clearance in healthy men who had fasted for 36 h 13 . Similarly, a reduction in clearance of roughly 15% was found in men who had fasted for 36 h 14 . Overall, both in animals and humans an apparent effect of malnutrition is increased exposure to total acetaminophen due to a decreased clearance, clinically presented as an increased t½.…”
Section: Discussionmentioning
confidence: 96%
“…10 In horses, low dosed acetaminophen clearance was reduced by 19% after the horses had been fasted for 72 h. 11 Mehta et al 12 showed a significant decrease in therapeutically dosed acetaminophen clearance in children suffering from protein-calorie malnutrition, resulting in a doubled t½ of 8.14 (±1.30) h compared to 4.33 (±0.52) hours in healthy age-matched controls. A recent study showed a ~10% decrease in therapeutically dosed acetaminophen clearance in healthy men who had fasted for 36 h. 13 Similarly, a reduction in clearance of roughly 15% was found in men who had fasted for 36 h. 14 Overall, both in animals and humans an apparent effect of malnutrition is increased exposure to total acetaminophen due to a decreased clearance, clinically presented as an increased t½.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of factors regulate the synthesis of albumin, including nutritional status, cytokines and hormones. 20 In one study, 21 short-term fasting increased acetaminophen exposure in healthy subjects administered oral acetaminophen at 1000 mg. However, in another study including 197 subjects, 6 overweight-obesity status was a significant risk factor for acute liver injury secondary to acute acetaminophen overdose.…”
Section: Discussionmentioning
confidence: 99%